White Maize (Zea mays L.): An Emerging Option for Crop Diversification and Nutritional Security - Mukri, Ganapati; Singh, Chandu; Naik, K. Bhojaraja; Yalamalle, V. R.; Babu, Subhash (Chronicle of Bioresource Management, 2023)
Maize is the third most important cereal after wheat and rice and the major chunk of maize production is used as poultry and animal feed in India. But for direct human consumption white maize is preferred. Hence, from the human nutritional point of view, there is a need to improve the nutritional value of white maize. Genetically both yellow and white maize is the same except for genes coding the β-carotene, which imparts a golden yellow color to the maize. The white maize breeding program started during the 1960s, resulting in the release of ‘Ganga safed 2’, which is still popular among farmers. The future breeding prospects and the role of quality protein maize (QPM) in nutrition and value additions are very important aspects.